112 Healthcare Utilization and Costs for Patients With Tardive Dyskinesia. (15th June 2018) - Carroll, Benjamin; Juneau, Paul; Irwin, Debra
Abstract: Introduction: Tardive dyskinesia (TD) is an often-irreversible movement disorder that usually results from prolonged use of antipsychotics. Although the burden of TD on patients' quality of life has been reported, there is limited evidence of its impact on the healthcare system. Objective: To assess healthcare utilization and costs between TD and non-TD patients in a sample of patients from the commercially insured and Medicare Supplemental US populations. Methods: A retrospective cohort analysis was conducted using Truven MarketScan Commercial/Medicare claims data. For each patient included in the analysis, the index date was set as the first TD diagnosis between 1/1/2008 and 9/30/2014. Patients with TD were then matched to similar patients without TD to compare resource utilization andcosts. Descriptive statistics on the incidence of resource utilization and costs of healthcare were reported. Results: A total of 1020 patients were included in this analysis. TD patients had significantly greater annual all-cause (TD: $54, 656; non-TD: $28, 777) and mental health-related (TD: $10, 199; non-TD: $2, 605) healthcare costs compared with non-TD patients (P<0.01). This was primarily because a higher proportion of the TD patientsexperienced hospitalizations (all-cause 56%; mental health 17%) and emergency room visits (all-cause 62%; mental health 27%) compared with non-TD patients(hospitalizations: all-cause 26%, mental health 5%; emergency room visits: all-cause 41%; mental health 13%) (all P<0.001). Conclusions: Patients identified as being diagnosed with TD demonstrate significantly higher healthcare utilization and costs in the 12 months after diagnosis than do similar patients without TD. Presented at: Psych Congress; September 16–19, 2017; New Orleans, Louisiana, USA. Funding Acknowledgements: This study was funded by Teva Pharmaceutical Industries, Petach Tikva, Israel.